Schizophrenia in childhood - Ericksen, Glenda Joy (Department of Paediatrics and Child Health, 2017)
The diagnosis of Schizophrenia in children has historically been the source of much psychiatric controversy, especially with regard to classification, treatment and prognosis. This was further complicated by the broad category for the diagnosis of psychotic disorders in childhood in the Diagnostic and Statistical Manual of Mental Disorders (DSM 11).This included Schizophrenia in childhood, autism, and other psychotic conditions. The work of Kolvin (1971 a-f) and Rutter (1972), have been instrumental in separating autism and Schizophrenia into distinct categories. This review is not aimed at being an exhaustive coverage of all the literature on Schizophrenia in childhood, but is focused on classification, phenomenology, epidemiology, differential diagnosis, etiology, course, cross-cultural factors, and treatment. The adult literature has been referred to, when there is no appropriate reference in the literature on children with Schizophrenia, in certain focused areas. Specific research questions will be discussed in depth in the appropriate sections. These are: 1) Is Schizophrenia with childhood onset a discretely homogenous entity or is the condition on a continuum with adult Schizophrenia? 2) Are the current classification systems diagnostically valid in children with Schizophrenia? 3) Do phenomenological descriptions of the condition assist the clinician diagnostically, given the financial constraints limiting the extent of special investigations, in the South African context? 4) The evidence concerning the etiology of Schizophrenia in childhood will be critically evaluated. 5) Do current treatment models have any relevance to clinical practice in South Africa, especially with regard to the need for cost-effective solutions? 6) Two cases obtained from the in-patient Unit of the Red Cross Hospital's Child and Family Unit will also be examined, in the light of the literature. As much of the literature prior to DSM III generally did not clearly differentiate between childhood Schizophrenia, autism and other heterogeneous conditions (Rutter, 1972), they have not been included, except for seminal papers. In addition the age groups in the papers do not always mention the pubertal status of the children, thus for the purpose of the review, primarily studies focusing on samples with onset prior to 13 years are included. These have lately been characterized in the literature as 'VEOS' (Very Early Onset Schizophrenia). In one of the few longitudinal studies of children with Schizophrenia, Werry, McClellan and Chard (1991), reported that more than half the sample (55%) which had been diagnosed as schizophrenic at first presentation, was found to have Bipolar Disorder at follow-up. It is possible that the papers reviewed may also reflect this once longitudinal follow-up has been completed. The results of longitudinal studies are awaited.